Foundation Retrofitting Using Micropiles - A Case History - Mohammad Nasim (Deep Foundations Institute, 2008)
Vertical expansion of existing structures frequently requires foundation retrofitting to enhance the capacity of existing foundations for supporting additional loads. Owing to their small diameter, a variety of suitable drilling methods available for installation, and smaller installation equipment capable of operating under limited headroom conditions, micropiles are often preferred for foundation retrofitting. This paper presents a case history demonstrating application of micropiles to underpin the existing foundation of the Washington D.C. Children?s National Medical Center (CNMC) for its future expansion. Located at 111 Michigan Avenue in northwest Washington, DC, portions of the hospital currently extend five stories above grade and three levels below-grade as parking garages. The hospital intends to expand the surgical wing up to the current build out (five stories) above the remaining portion of the existing parking garage. The original foundations consist of 80-ton Raymond Step-Tapered piles. New loading on the foundations required each Raymond pile to be capable of supporting 150 tons. Results from quick load tests on existing piles indicated that two entire column lines (Column Line A and B) would experience loads beyond their capacity, requiring enhancement of the existing foundation at these locations. The design and construction of the foundation upgrading work was particularly challenging due to various project constraints related to a high groundwater table, micropile installation under limited head room, and ensuring that the parking garage remained fully operational for the entire duration of construction. The paper presents the challenges faced during testing of existing foundations amid a high groundwater table, design developments of underpinning options to support the additional column loads, difficulties and challenges encountered during installation of the micropiles and construction of the micropile pilecaps, and value engineering options developed during various phases of the project. Understanding that micropiles are often a preferred option for foundation retrofitting, the case history is expected to provide a baseline design approach and innovative solutions to typical challenges faced during construction, thereby reducing potential cost overruns during design development and construction of similar future projects.